Tunable metasurfaces and metadevices - Zou, Chengjun; Staude, Isabelle; Neshev, Dragomir N. (Elsevier, 2019)
We review the fundamentals and recent advances in the field of tunable dielectric metasurfaces. In particular, we discuss the mechanisms of tuning for dielectric metasurfaces, including changing of the metasurface geometry, changing of the resonators material and their surrounding. We also present several examples of functional tunable metadevices based on dielectric metasurface, including lenses with tunable focal length and switchable beam deflectors.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Dielectric metasurface; Liquid crystals; Tunable metasurfaces